The Paradox of Astroglial Ca2 + Signals at the Interface of Excitation and Inhibition - Caudal, Laura C.; Gobbo, Davide; Scheller, Anja; Kirchhoff, Frank (Frontiers in Cellular Neuroscience, 2020)
Astroglial networks constitute a non-neuronal communication system in the brain and are acknowledged modulators of synaptic plasticity. A sophisticated set of transmitter receptors in combination with distinct secretion mechanisms enables astrocytes to sense and modulate synaptic transmission. This integrative function evolved around intracellular Ca2+ signals, by and large considered as the main indicator of astrocyte activity. Regular brain physiology meticulously relies on the constant reciprocity of excitation and inhibition (E/I). Astrocytes are metabolically, physically and functionally associated to the E/I convergence. Metabolically, astrocytes provide glutamine, the precursor of both major neurotransmitters governing E/I in the central nervous system (CNS): glutamate and γ-aminobutyric acid (GABA). Perisynaptic astroglial processes are structurally and functionally associated with the respective circuits throughout the CNS. Astonishingly, in astrocytes, glutamatergic as well as GABAergic inputs elicit similar rises in intracellular Ca2+ that in turn can trigger the release of glutamate and GABA as well. Paradoxically, as gliotransmitters, these two molecules can thus strengthen, weaken or even reverse the input signal. Therefore, the net impact on neuronal network function is often convoluted and cannot be simply predicted by the nature of the stimulus itself. In this review, we highlight the ambiguity of astrocytes on discriminating and affecting synaptic activity in physiological and pathological state. Here, we gather recent evidence on the complexity of astroglial Ca2+ signals in health and disease, challenging the traditional, neuro-centric concept of segregating E/I, in favor of a non-binary, mutually dependent perspective on glutamatergic and GABAergic transmission.